Anatomical Variation of Right Coronary Artery: A Retrospective Coronary Angiographic Study - Srivastava, Isha; Sharma, Hina; Goswami, Divyesh; Sahi, Disha (Journal of Neonatal Surgery, 2025)
Background: The right coronary artery (RCA) plays a crucial role in cardiac perfusion, and its anatomical variations can have significant diagnostic and therapeutic implications, particularly in coronary interventions and cardiac surgeries. This study aimed to evaluate the prevalence and pattern of anatomical variations in the RCA based on coronary angiographic findings in a tertiary care center. Material and Methods: A retrospective observational study was conducted over a 2-year period, involving 500 patients who underwent coronary angiography for various clinical indications. Demographic details, RCA origin, course, branching pattern, and dominance were recorded and analyzed using standard angiographic views. Data were expressed as frequencies and percentages. Results: The majority of patients were male (65.6%), with most participants aged between 46 and 60 years (39.2%). A normal origin of the RCA from the right aortic sinus was observed in 93.6% of cases. Anatomical variations included high origin from the ascending aorta (2.8%), separate conus branch origin (2.0%), origin from the left coronary sinus (0.8%), and pulmonary artery origin (0.8%). Right coronary dominance was most common (82.4%), followed by left (10.4%) and co-dominance (7.2%). Normal RCA morphology was present in 87.6% of cases, with variations such as early branching (5.6%), duplication (2.4%), myocardial bridging (1.6%), and ectopic origin (2.8%) observed. The leading indications for angiography included chronic stable angina (39.6%), acute coronary syndrome (24.8%), ST-elevation myocardial infarction (21.2%), and preoperative evaluation (14.4%). Conclusion: Anatomical variations of the RCA, though uncommon, are clinically relevant and must be recognized during diagnostic and interventional procedures. Awareness of these variations can aid in accurate diagnosis, procedural planning, and improved patient outcomes.